Research method of the synonymy phenomenon of family lexemes on the basis of the communicative and activity approach - Rudiuk, Tetiana (ScienceRise: Pedagogical Education, 2020)
The article is about the theoretical analysis of methodological, pedagogical, psychological, professional and other literature on the problem of the study of the phenomenon of synonymy of related lexemes and methods of teaching them on the basis of communicative-activity approach. There was determined the initial level of ownership of such concepts as «family vocabulary» and «synonymy of related lexemes», practical skills of constructing own utterances, the ability to use synonyms-correspondences in a creative context were clarified. A system of exercises has been developed that aims at developing empathy in the classroom, friendliness and ability to understand one another more deeply, to be able to pick up synonyms for these units, and explain their lexical meaning. There was introduced and realized a number of psychological and rehabilitation exercises in the class family, the skills of forgiving and asking for forgiveness. Among the conditions that ensured the effectiveness of the communicative activity approach there was the creation of a favorable psychological microclimate of the team, comfort and acceptance of each of its members individually. It was shown the importance to support humanity and tolerance towards the participants of the educational process and for each individual personally. The system of intersubject links is implemented in the context of a certain algorithm of actions, namely: before, directly, and after the exercise. The self-reflection stage is closely linked to the language material in the lesson. There were discussed semantic shades of synonyms of family vocabulary and variants of their use in certain situations of associative experiments. The creative use of IT in the context of the study synonymy of family vocabulary, based on the communicative-activity approach, is proposed